Development and validation of novel digitalized cervicography system - Kim, Soo-Nyung; Kim, Yun Hwan; Nam, Kye-Hyun; Lee, Seon-Kyung; Lee, Tae Sung; Choi, Ho-Sun; Han, Sei-Jun; Kim, Seung-Cheol (Obstetrics & gynecology science, 2016)
Digital cervicography systems would be expected to reduce the costs of film cervicography, and provide the opportunity for "telemedicine-based" screening. We aimed to develop web-based digital cervicography system, and validate it compared with conventional film cervicography. A hundred cases from five centers were prospectively included, and cervical images (analogue, digitalized by scanning analogue, and digital) were taken separately using both analogue (Cerviscope) and digital camera (Dr. Cervicam) in each patient. Nine specialists evaluated the three kinds of images of each case with time interval between evaluations of each image. To validate novel digitalized system, we analyzed intra-observer variance among evaluation results of three kinds of images. Sixty-three cases were finally analyzed after excluding technically defective cases that cannot be evaluable on analogue images. The generalized kappa for analogue versus digital image was 0.83, for analogue versus scanned image 0.72, and for digital versus scanned image was 0.71; all were in excellent consensus. Digitalized cervicography system can be substituted for the film cervicography very reliably, and can be used as a promising telemedicine tool for cervical cancer screening.